Adaptive innovation in the evolution of a latecomer firm: The case of Asiainfo, China - Zhou, S.; Baskaran, A.; Tang, M.; Rasiah, R. (Faculty of Economics and Administration, University of Malaya, 2017)
This paper is based on a case study of AsiaInfo, a latecomer telecommunications software and service firm in China. It examines whether and how adaptive innovation can enable the latecomer firms in developing countries to accumulate technological advantages and gain competitiveness to emerge as multinational enterprises (MNEs) Data for this study is obtained from a series of interviews with managers in AsiaInfo and China Mobile. This study applied an evolutionary approach to analyse complex and dynamic developments within AsiaInfo and found that the firm (AsiaInfo) has: (i) gradually obtained its competitive advantages through continuous accumulations of adaptive innovations over 20 years; (ii) accumulated adaptive innovations and its competitive advantage co-evolved with the rapidly growing demands of the Chinese telecommunication industry; and (iii) the ability to continuously generate adaptive innovations depended not only on its ability to accumulate technological innovations, but also social and organisational innovations. These factors were instrumental in enabling AsiaInfo to eventually emerge as a multinational enterprise and catch-up with other multinationals. This case study makes a significant contribution to the growing body of literature on latecomer firms’ characteristics and strategies, particularly in East Asia. It makes a theoretical contribution by modifying Michael Porter’s diamond model and integrating it with latecomer strategies that treat adaptive innovation as central for achieving competitive advantages.